Pengaruh Lingkungan Kerja dan Fasilitas Kerja Terhadap Loyalitas Karyawan Dengan Kepuasan Kerja Sebagai Variabel Pemediasi - Dimas Putranugraha (JURNAL ILMIAH EDUNOMIKA, 2021)
Having loyal employees is an advantage for the company, therefore it is important to know the antecedents of loyalty. This study aims to examine job satisfaction as a mediating variable on the influence of work environment and work facilities on loyalty. The study was conducted on 52 employees of PT Abadi Bina Indonesia Yogyakarta. Primary data taken using questionnaires were processed with multiple regression analysis and Sobel test. The findings show that job satisfaction is able to mediate the influence of the work environment on loyalty. Likewise, job satisfaction is able to mediate the effect of work facilities on employee loyalty. Keywords: work environment, work facilities, job satisfaction, employee loyalty.